Heme interplay between IlsA and IsdC: Two structurally different surface proteins from Bacillus cereus - Abi-Khalil, Elise; Segond, Diego; Terpstra, Tyson; André-Leroux, Gwenaëlle; Kallassy, Mireille; Lereclus, Didier; Bou-Abdallah, Fadi; Nielsen-Leroux, Christina (Biochimica et biophysica acta, 2015)
Iron is an essential element for bacterial growth and virulence. Because of its limited bioavailability in the host, bacteria have adapted several strategies to acquire iron during infection. In the human opportunistic bacteria Bacillus cereus, a surface protein IlsA is shown to be involved in iron acquisition from both ferritin and hemoproteins. IlsA has a modular structure consisting of a NEAT (Near Iron transporter) domain at the N-terminus, several LRR (Leucine Rich Repeat) motifs and a SLH (Surface Layer Homology) domain likely involved in anchoring the protein to the cell surface. Isothermal titration calorimetry, UV–Vis spectrophotometry, affinity chromatography and rapid kinetics stopped-flow measurements were employed to probe the binding and transfer of hemin between two different B. cereus surface proteins (IlsA and IsdC). IlsA binds hemin via the NEAT domain and is able to extract heme from hemoglobin whereas the LRR domain alone is not involved in these processes. A rapid hemin transfer from hemin-containing IlsA (holo-IlsA) to hemin-free IsdC (apo-IsdC) is demonstrated. For the first time, it is shown that two different B. cereus surface proteins (IlsA and IsdC) can interact and transfer heme suggesting their involvement in B. cereus heme acquisition. An important role for the complete Isd system in heme-associated bacterial growth is demonstrated and new insights into the interplay between an Isd NEAT surface protein and an IlsA-NEAT-LRR protein, both of which appear to be involved in heme-iron acquisition in B. cereus are revealed. •The NEAT domain of IlsA is shown to bind hemin and extract heme from hemoglobin.•The IlsA LRR domain alone cannot bind hemoglobin or hemin.•Holo-IlsA (hemin-loaded) is able to donate hemin to apo-IsdC (hemin-free).•IlsA and IsdC can interact suggesting a role in heme acquisition by B. cereus.•The B. cereus Isd system is involved in heme-iron acquisition.